Performance of Mixed Cropping of Lentil with Cowpea Under Variable Seeding Ratios - Farhad, ISM; Jahan, E; Rahman, MA; Azam, MG; Mujahidi, TA (Bangladesh Agronomy Journal, 2018)
The field experiment was carried out at South Lemua, MLT site, Feni (AEZ 19) during Rabi season of 2015-16 to evaluate the performance of lentil as mixed crop with cowpea under variable seeding ratio. The treatment combinations used for the experiment were T1= Sole Lentil (100 %) @ 40 kg seed ha-1, T2 =Sole Cowpea (100%) @ 45kg seed ha-1, T3 = Lentil (100%) + Cowpea (10 %), T4 = Lentil (100 %) + Cowpea (20 %) and T5 = Lentil (100 %) + Cowpea (30 %). Lentil var. BARIMashur-6 and cowpea variety BARI Felon-1 were used in this study. The yield of lentil decreased with the increase of cowpea population in the mixed cropping situation. All the mixed cropping combinations showed higher lentil equivalent yield (LEY), land equivalent ratio (LER), net return and benefit cost ratio (BCR) than sole cropping. The highest lentil equivalent yield (1438 kg ha-1) and maximum land equivalent ratio (1.24) were observed in T4 treatment. Cost and return analysis showed that the highest net return (Tk. 77,890 ha-1) was found in T4 treatment while sole cowpea gave the lowest net return (Tk. 7530 ha-1). The highest benefit cost ratio (3.09) was recorded from lentil (100 %) + cowpea (20 %) whereas the minimum (1.21) from sole cowpea. Bangladesh Agron. J. 2018, 21(1): 125-129